The Role of Educational Level and Cognitive Status in Men Undergoing Artificial Urinary Sphincter Implantation REPLY - Keles, Ahmet; Onur, Rahmi; Aydos, Murat; Dincer, Murat; Koca, Orhan; Coskun, Burhan; Karakeci, Ahmet (Elsevier Science Inc, 2021)
[Abstract Not Available]